1991
DOI: 10.1111/j.1469-7998.1991.tb04330.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase delay of the natural photoperiod alters reproductive timing in the marsupial Antechinus stuartii

Abstract: The dasyurid marsupial Antechinus stuartii (20–40 g) has a brief, highly synchronized mating period in spring followed by complete male mortality. Analysis of breeding times in nature suggests that the rate of change of photoperiod is the main Zeitgeber for reproductive timing in this species. To test this hypothesis the natural photoperiod was phase delayed by two months, one experiment beginning in late summer, and the other in the autumn, before the spring breeding period. The reproductive cycle of males an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…We studied 12 adult, female S. macroura (body mass 24:0 AE 3:0 g) that were captivebred at the University of New England in Armidale. Individual reproductive condition was classified following McAllan et al (1991). When exhibiting oestrus, each female was paired with a male for the duration of the oestrous period.…”
mentioning
confidence: 99%
“…We studied 12 adult, female S. macroura (body mass 24:0 AE 3:0 g) that were captivebred at the University of New England in Armidale. Individual reproductive condition was classified following McAllan et al (1991). When exhibiting oestrus, each female was paired with a male for the duration of the oestrous period.…”
mentioning
confidence: 99%
“…Females were checked once every 1-2 weeks and during the mating season every 2-3 days, for the presence of epithelial cells, which indicate the onset of oestrus (Selwood 1982;McAllan et al 1991). Urine samples were taken when possible.…”
Section: Femalesmentioning
confidence: 99%
“…Dickman (1985) found that the laboratory conditions of his study also affected reproductive synchrony under both naturally changing and LD 12:12 photoperiod, indicating an effect of social organization. McAllan and Dickman (1986) and McAllan et al (1991) demonstrated that a discretely increasing photoperiod (rate of change of photoperiod) may synchronize reproduction in A. stuartii.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations